Kontribusi Agroforestry Terhadap Pendapatan Petani Desa Nekbaun, Kecamatan Amarasi Barat, Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Bartolomeus Telaumbanua; Maria M. E. Purnama; Wilhelmina Seran (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
This research was carried out with the aim of knowing the composition of plant types the make up Agroforetryand the amount of contribution to income and the agroforestry system in Nekbaun Village, West Amarasi Distreat, Kupang Regency, East Nusa Tenggara Province. Sample selection was carried out purposively. Data collection techniques were carried out in this research, namely primary data and secondary data. From the results obtained, analysis was carried out using qualitative descriptive and quantitative descriptive analysis. The data is processed using income analysis formulas, percentages, income and expenditure data. The research results, it is know that the agroforestry system implemented in Nekbaun Village ia an agroforestry system that has been implemented for generation and still uses a traditional system, namely using forestry garden plants anso livestrock, whice is often referred to as, agrosilfopasture. The composition of the types of plants that make up agroforestry in Nekbaun Village consists of Bananas (Musa), Corn (Zea Mays), Coconut (Cocos Nucifera), Mahogany (Swietenia Mahagoni), and Teak (Tektona Grandis). The income contribution obtained by farmers in Nekbaun Village from agroforestry results is IDR 10.454.939/year.